Combined GM‐CSF and G‐CSF administration mobilizes CD4+CD25hiFoxp3hi Treg in leukapheresis products of rhesus monkeys. Issue 6 (20th January 2020) - Sasaki, Kazuki; Wang, Yu‐Chao; Lu, Lien; Hughes, Julia; Vujevich, Veronica; Thomson, Angus W.; Ezzelarab, Mohamed B.
Abstract : Early phase clinical trials are evaluating the feasibility, safety, and therapeutic potential of ex vivo expanded regulatory T cells (Treg) in transplantation. A limitation is the paucity of naturally occurring Treg numbers in peripheral blood. Hence, protracted ex vivo expansion is required to obtain sufficient Treg in order to meet target cell doses. Because cytokine administration has been used successfully to mobilize immune cells to the peripheral blood in experimental and clinical studies, we hypothesized that granulocyte macrophage–colony‐stimulating factor (GM‐CSF) and granulocyte‐CSF (G‐CSF) administration would enhance Treg percentages in leukapheresis products of rhesus monkeys. Following combined GM‐CSF and G‐CSF administration, the incidence of Treg in peripheral blood and leukapheresis products was elevated significantly, where approximately 3.7 × 10 6 /kg CD4 + CD25 hi Foxp3 hi or 6.8 × 10 6 /kg CD4 + CD25 hi CD127 lo Treg can be collected from individual products. Mobilized Treg expressed a comparable repertoire of surface markers, chemokine receptors, and transcription factors to naïve monkey peripheral blood Treg. Furthermore, when expanded ex vivo, mobilized leukapheresis product and peripheral blood Treg exhibited similar ability to suppress autologous CD4 + and CD8 + T cell proliferation. These observations indicate that leukapheresis products from combined GM‐CSF‐ and G‐CSF‐mobilized individuals are a comparatively rich source of Treg and may circumvent long‐term ex vivo expansion required for therapeutic application. Abstract : In rhesus monkeys, combined GM‐CSF and G‐CSF administration enhances the incidence of regulatory T cells (Tregs) in leukapheresis products, which can be used a rich source of peripheral blood Tregs.